Antibiotics in agriculture – application, threats and legal regulations - Gawryjołek, Karolina (Polish Journal of Agronomy, 2021)
The discovery of the first antibiotic has become one of the most important medical advances. Since this time, a pe- riod of intensive research into antimicrobial substances has be- gun, which are also used in veterinary medicine and agricultural production. In animal production, antibiotics have therapeutic, as well as prophylactic and metaphylactic applications aimed at preventing bacterial diseases. They were also used as growth stimulants, which positively influenced, among others, for weight gain and more efficient use of feed. This form of antibiotic use in animal production was legally banned in 2006 in all European Union countries. In the cultivation of plants, antibiotics are also used to combat plant pathogens. The use of antibiotic agents has many consequences, both positive and negative. The most impor- tant risk of antibiotics overusing is the spread of antibiotic resist- ant bacteria. Another effect is environmental pollution and the contamination of agricultural products. Due to these factors, the use of antibiotics in agriculture is regulated by appropriate legal regulations.